1998
DOI: 10.1093/ageing/27.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Are rates of ageing determined in utero?

Abstract: the associations between early growth and markers of ageing suggest that in some systems, ageing may be programmed by events in early life. A potential mechanism is the impaired development of repair systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 13 publications
5
93
1
3
Order By: Relevance
“…Specific implications of our findings include the direct relationship between DNA hypomethylation and aging, particularly within the context of the "fetal origins of adult disease hypothesis" (50,53,62). Moreover, as summarized by Maier and Olek (33a), considerable indirect evidence exists that aberrant DNA methylation plays a role in the development of insulin resistance, not the least of which is finding of increased SAH levels in diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…Specific implications of our findings include the direct relationship between DNA hypomethylation and aging, particularly within the context of the "fetal origins of adult disease hypothesis" (50,53,62). Moreover, as summarized by Maier and Olek (33a), considerable indirect evidence exists that aberrant DNA methylation plays a role in the development of insulin resistance, not the least of which is finding of increased SAH levels in diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…Contudo, a associação da desnutrição precoce com o aumento da pressão intra-ocular não foi evidenciado (12) . Baixo peso no primeiro ano de vida tem sido associado com aumento da opacidade cristaliniana, surdez, diminuição de força e alterações dermatológicas (13) . Há evidências que a restrição da dieta instituída em útero ou precocemente após o nascimento pode ter um efeito oposto e está associado com o envelhecimento.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Low birth weight and shorter birth length were associated with increased mortality risk between 39 and 49 years of age in Danish men [5]. A large-scale cohort study has indicated that in men and women aged 64-74 years, nuclear lens opacities, reduced grip strength and impaired auditory ability were more common in individuals of lower weight at age 1 year, suggesting associations between early life events and the ageing process in humans [6,7].…”
Section: Introductionmentioning
confidence: 99%